Determinants of Investment Timing of Government Venture Capital Guiding Funds in China - Jing Cui; Shuqin Zhang; Xianan Yin; Kun Xu (Discrete Dynamics in Nature and Society)
With the prosperity of venture capital, all kinds of government venture capital guiding funds have sprung up, and the scale is explosive growth. However, the current investment of government guiding funds in enterprises has not fundamentally solved the financial difficulties in the early development of enterprises. This study examines the determinants of investment timing of government guiding funds. We investigate this question using the data of China’s new three board companies that have been invested by government guiding funds in the year of 2015-2016. We find that government guiding funds enter the enterprises into developed areas earlier. The innovation ability and the market competitiveness of the invested enterprises are positively correlated with the investment timing of government guiding funds. There is no significant relationship between the investment proportion of government guiding funds and the timing of entering the enterprises. The research of this paper can provide theoretical reference for the subsequent optimization of the resource allocation and provide ideas and methods for the policy improvement and management optimization of government venture capital guiding funds in the future.